Pimpinella enguezekensis (Apiaceae), a new species from East Anatolia Region (Turkey) - Yeşil, Yeter; Yildirim, Hasan; Akalin, Emine; Pirhan, Ademi Fahri; Altioğlu, Yusuf (Phytotaxa, 2016)
The new species Pimpinella enguezekensis (Apiaceae) is described from Ağılbaşı village (Engüzek), Darende district in Malatya city (E of Turkey). It shows a unique combination of morphological characteristics concerning the size, shape and margins of leaves, the indumentum of petals and the morphology of fruits. It is related to Pimpinella species with entire leaves and yellow flower, such as P. flabellifolia, P. paucidentata, P. sintenisii and P. nephrophylla of section Reutera subsection Flabellifoliae. The new species is more closely related to P. flabellifolia, with which it shares some morphological similarities, but from which it is easily distinguished by its multi-stemmed habit, smaller rhomboid leaves with spiny dentate margins, glabrous petals, and smaller fruits lacking ribs. According to micromorphological studies, fruits of P. enguezekensis are glabrous and show reticulate striate surface. Furthermore, they also show remarkable anatomical differences with regard to fruits of P. flabellifolia, the commissure width in P. enguezekensis being more than twice smaller than in P. flabellifolia and the mericarp length/width ratio in P. enguezekensis being also smaller than in P. flabellifolia. An identification key of the yellow-flowered species with entire leaves is reported. Moreover, a distribution map for P. enguezekensis and other Turkish yellow-flowered related species is presented.